Metode Numbered Heads Together Dalam Pembelajaran Untuk Meningkatkan Keaktifan Siswa - Ziyada, Rifalda Nur; Sobirin; Septiyani; Farida, Nur Aini; M. Makbul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
The aim of the research is to increase the activeness of PAI learning using the NHT (Numbered Head Together) model. Data collection uses observation and test sheets to determine student understanding. The results of research based on initial data show that students are not interested in learning using the lecture method, whereas when using the NHT method in both cycles it shows an increase. The first cycle of research showed results of 89.16% and the second cycle showed results of 94.16%, so it was stated that this research could increase learning activity.